Improved protocol for the radiosynthesis of [18F]FTC‐146: A potent and selective sigma‐1 receptor radioligand. (16th March 2023) - Sadeghzadeh, Masoud; Wenzel, Barbara; Nikodemus, Julia; Florea, Alexandru; Hertel, Fabian; Kopka, Klaus; Vogg, Andreas T. J.; Kiessling, Fabian; Mottaghy, Felix M.
Abstract : [ 18 F]FTC‐146 was introduced as a very potent and selective sigma‐1 receptor radioligand, which has shown promising application as an imaging agent for neuropathic pain with positron emission tomography. In line with a multi‐laboratory project on animal welfare, we chose this radioligand to investigate its potential for detecting neuropathic pain and tissue damage in tumor‐bearing animals. However, the radiochemical yield (RCY) of around 4–7% was not satisfactory to us, and efforts were made to improve it. Herein, we describe an improved approach for the radiosynthesis of [ 18 F]FTC‐146 resulting in a RCY, which is sevenfold higher than that previously reported. A tosylate precursor was synthesized and radio‐fluorination experiments were performed via aliphatic nucleophilic substitution reactions using either K[ 18 F]F‐Kryptofix®222 (K2.2.2 )‐carbonate system or tetra‐n‐butylammonium [ 18 F]fluoride ([ 18 F]TBAF). Several parameters affecting the radiolabeling reaction such as solvent, 18 F‐fluorination agent with the corresponding amount of base, labeling time, and temperature were investigated. Best labeling reaction conditions were found to be [ 18 F]TBAF and acetonitrile as solvent at 100°C. The new protocol was then translated to an automated procedure using a FX2 N synthesis module. Finally, the radiotracer reproducibly obtained with RCYs of 41.7 ± 4.4% in high radiochemical purity (>98%) and molar activities up to 171 GBq/μmol. Abstract : [ 18 F]FTC‐146 was introduced as a very potent and selective sigma‐1 receptor radioligand. However, the radiochemical yield (RCY) of around 4–7% may have been a limiting factor in further applicability of this radiotracer. We described an optimized fully automated radiosynthesis approach afforded [ 18 F]FTC‐146 in over sevenfold higher RCYs.